2014
DOI: 10.1371/journal.pone.0110689
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Analysis of Cytokinesis In Situ during C. elegans Postembryonic Development

Abstract: The physical separation of a cell into two daughter cells during cytokinesis requires cell-intrinsic shape changes driven by a contractile ring. However, in vivo, cells interact with their environment, which includes other cells. How cytokinesis occurs in tissues is not well understood. Here, we studied cytokinesis in an intact animal during tissue biogenesis. We used high-resolution microscopy and quantitative analysis to study the three rounds of division of the C. elegans vulval precursor cells (VPCs). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…Heat-shock treatment did not cause defects in embryonic viability or inhibit larval development in wild-type (WT) animals; however, the conditional ani-1 mutant embryos exhibited embryonic lethality with penetrances of 55% (ani-1-sg1) and 35% (ani-1-sg2) and larval arrest phenotypes in 18% of ani-1-sg1 and 35% of ani-1-sg2 animals ( Figure 1G), which are consistent with the phenotypes of ani-1 RNAi animals. C. elegans ANI-1 was previously reported to be dispensable for cytokinesis in early embryos, whereas recent studies showed that ANI-1 is essential for cytokinesis in embryonic neuroblasts and vulval precursor cells [16,17,21,27]. We first determined whether ANI-1 regulates Q neuroblast division.…”
Section: Generation Of Conditional Knockouts Of Anillin Using Somaticmentioning
confidence: 99%
“…Heat-shock treatment did not cause defects in embryonic viability or inhibit larval development in wild-type (WT) animals; however, the conditional ani-1 mutant embryos exhibited embryonic lethality with penetrances of 55% (ani-1-sg1) and 35% (ani-1-sg2) and larval arrest phenotypes in 18% of ani-1-sg1 and 35% of ani-1-sg2 animals ( Figure 1G), which are consistent with the phenotypes of ani-1 RNAi animals. C. elegans ANI-1 was previously reported to be dispensable for cytokinesis in early embryos, whereas recent studies showed that ANI-1 is essential for cytokinesis in embryonic neuroblasts and vulval precursor cells [16,17,21,27]. We first determined whether ANI-1 regulates Q neuroblast division.…”
Section: Generation Of Conditional Knockouts Of Anillin Using Somaticmentioning
confidence: 99%
“…To compare simulation results with in vivo data, we acquired optical sections throughout the thickness of C. elegans zygotes, rotated image data sets 90 degrees to observe the 7 entire division plane, visualized with a fluorescently-tagged ring component, and used custom Matlab-based software to annotate the position of the cytokinetic ring over time ( Figure 1D, E; (Dorn et al, 2010)). As in silico, the ring closed in an average of 5 minutes, accelerating until approximately half closed, and then decelerating ( Figure 1F, F'; (Bourdages et al, 2014)). Thus, simulated control rings and rings visualized in vivo exhibited similar closure dynamics, suggesting that our in silico approach using bipolar motor ensembles faithfully recapitulates some aspects of in vivo ring dynamics.…”
Section: Simulated Actomyosin Rings With Nmm-ii-like Motor Ensembles mentioning
confidence: 63%
“…Anaphase onset was determined by observing a separation between chromatin masses visible against the background of myosin fluorescence in the spindle. Ring closure was determined using semi-automated custom software cyanRing (for CYtokinesis ANalysis of the RING) as described previously (Dorn et al, 2010;Bourdages et al, 2014). In cyanRing, the equatorial region of the embryo is cropped from the 3D image stack, rotated, and maximum-intensity projected to produce a view of the cytokinetic ring along the spindle axis as viewed from the posterior direction.…”
Section: Measurements Of Ring Closurementioning
confidence: 99%
“…During each of the first three divisions of the C. elegans embryo, there is a substantial period following the onset of ring constriction when the overall rate of ring closure remains approximately constant despite the fact that the ring is progressively decreasing in size (Zumdieck et al 2007;Carvalho et al 2009;Bourdages et al 2014). Thus the per-unit-length rate of closure increases as the circumference decreases.…”
Section: Contractile Ring Assembly and Dynamicsmentioning
confidence: 99%